Infrastructure Readiness for Blended Learning Education Business in Indonesia After Covid-19 - Gayatri, Anindita (Journal Management SMC, 2025)
This research is conducted to find the most suitable digital platform for blended learning business in Indonesia by analyzing the proportion population of desktop and mobile device owners for 9 years within 2015 to 2023. The data used for the analysis is quantitative and sourced from the dataset of Indonesian Statistic (BPS). It aims to give a better decision for education business players in choosing digital platform by province in Indonesia. The results of the study prove a significant mobile platform growth which cannot be caught up by desktop platform for most of the provinces. But surprisingly besides Java and Bali, these provinces have the highest proportion users of both desktop and mobile devices among other provinces i.e. The Riau Islands, North Kalimantan and East Kalimantan.